Fabrication of high-performance Ba0.95Ca0.05Ti0.85Zr0.15O3 ceramics by aqueous chemical coating method. (July 2015) - Shen, Zhengbo; Wang, Xiaohui; Gong, Huiling; Wu, Longwen; Li, Longtu
Abstract: Al2 O3 -coated Ba0.95 Ca0.05 Ti0.85 Zr0.15 O3 dielectric ceramics with excellent performance were fabricated by a novel aqueous chemical coating method. With this method, Al2 O3 was well coated on the surface of Ba0.95 Ca0.05 Ti0.85 Zr0.15 O3 powders, resulting in homogenous microstructure, excellent dielectric and electrical properties. The specimen with an appropriate coating amount of 0.4 wt% Al2 O3 exhibited the most outstanding properties. The dielectric constant at room temperature could reach 13, 600, with low dielectric loss ( 0.5%) and high insulation resistivity ( 6.2×10 11 Ω· cm). DC breakdown strength was also improved to 12.5 kV/mm because of Al2 O3 coating.